دور التسويق الرشيق في تحقيق التفوق التسويقي- دراسة تقييمة من زبائن موبيليس وأوريدو - طلوش, فارس (جامعة الوادي - University of Eloued, 2022)
يهدف هذا المقال إلى إبراز دور تطبيق التسويق الرشيق في تحقيق التفوق التسويقي للمؤسسات، في عالم يشهد التغير الشديد والتوجه إلى الإبداع والبحث عن كل جديد، أين تم تقييم ذلك على مؤسسات تنشط ضمن خدمة شبكة الهاتف النقال في الجزائر الذي يشهد منافسة شرسة ما بين ثلاثة مؤسسات، بتقييم إتباع الأساليب التسويقية الرشيقة من طرف زبائن مؤسستين وآثار ذلك على تفوقها التنافسي، أين تم إستجواب عينة تقدر ب140 زبون، وتم التوصل إلى تفوق تنافسي لمؤسسة على أخرى جراء إتباع أبعاد رشيقة للممارسات التسويقية. This article aims to highlight the role of the application of agile marketing in achieving marketing excellence for organizations in a world witnessing extreme change and the tendency to creativity and search for everything new, by evaluating the adoption of agile marketing methods by the customers of both dealers and the effects of this on their competitive advantage, where was a sample estimated at 140 customers questioned, and the competitive superiority of one customer over another was reached as a result of following agile dimensions of marketing practice
The role of agile marketing in achieving marketing excellence An evaluation study from Mobilis and Ooredoo customer
مقال
Keywords: التسويق الرشيق ، التفوق التسويقي.